Leaf Damage Based Phenotyping Technique and Its Validation Against Fall Armyworm, Spodoptera frugiperda (J. E. Smith), in Maize - Soujanya, P. Lakshmi; Sekhar, J. C.; Yathish, K. R.; Karjagi, Chikkappa G.; Rao, K. Sankara; Suby, S. B.; Jat, S. L.; Kumar, Bhupender; Kumar, Krishan; Vadessery, Jyothilakshmi; Subaharan, K.; Patil, Jagadish; et al. (Frontiers in Plant Science, 2022)
Globally maize is an important cereal food crop with highest production and productivity. Among the biotic constraints that limit the productivity of maize, the recent invasion of fall armyworm (FAW) in India is a concern. The first line of strategy available for FAW management is to evaluate and exploit the resistance genotypes for inclusion in the IPM schedule. Screening for resistant maize genotypes against FAW is in its infancy in India, considering its recent occurrence in the country. The present work attempts to optimise screening techniques suited to Indian conditions, which involve the description of leaf damage rating (LDR) by comparing injury levels among maize genotypes and to validate the result obtained from the optimised screening technique by identification of potential lines resistant to FAW under artificial infestation. Exposure of 20 neonate FAW larvae at V5 phenological stage coupled with the adoption of LDR on a 1-9 scale aided to characterise maize genotypes as resistant, moderately resistant and susceptible. The LDR varies with genotype, neonate counts and days after infestation. The genotypes, viz., DMRE 63, DML-163-1, CML 71, CML 141, CML 337, CML 346 and wild relative, Zea mays parviglumis recorded lower LDR ratings against FAW and can be exploited for resistance breeding in maize.